Predictors of the On-Road Driving Assessment After Traumatic Brain Injury: Comparing Cognitive Tests, Injury Factors, and Demographics. Issue 6 (November 2016) - McKay, Adam; Liew, Carine; Schönberger, Michael; Ross, Pamela; Ponsford, Jennie
Abstract : Objectives: (1) To examine the relations between performance on cognitive tests and on-road driving assessment in a sample of persons with traumatic brain injury (TBI). (2) To compare cognitive predictors of the on-road assessment with demographic and injury-related predictors. Participants: Ninety-nine people with mild-severe TBI who completed an on-road driving assessment in an Australian rehabilitation setting. Design: Retrospective case series. Main Measures: Wechsler Test of Adult Reading or National Adult Reading Test—Revised; 4 subtests from the Wechsler Adult Intelligence Scale-III; Rey Auditory Verbal Leaning Test; Rey Complex Figure Test; Trail Making Test; demographic factors (age, sex, years licensed); and injury-related factors (duration of posttraumatic amnesia; time postinjury). Results: Participants who failed the driving assessment did worse on measures of attention, visual memory, and executive processing; however, cognitive tests were weak correlates ( r values <0.3) and poor predictors of the driving assessment. Posttraumatic amnesia duration mediated by time postinjury was the strongest predictor of the driving assessment—that is, participants with more severe TBIs had later driving assessments and were more likely to fail. Conclusion: Cognitive tests are not reliable predictors of the on-road driving assessment outcome. Traumatic brain injury severity may be a better predictor of on-road driving; however, further research is needed to identify the best predictors of driving behavior after TBI.